Influence of structural inheritance on foreland-foredeep system evolution: An example from the Po valley region (northern Italy). (November 2016) - Turrini, Claudio; Toscani, Giovanni; Lacombe, Olivier; Roure, François
Abstract: Understanding the development of foreland-foredeep systems and the influence exerted by pre-existing structures on their evolution is an important step for defining the key factors that control long-term basin and lithosphere dynamics, comprehending the associated seismic hazard and assessing their economic potential in the domain of hydrocarbon exploration. The Po Valley is a rather unique foreland basin for two major reasons: a) it developed intermittently at the front of two different mountain chains, the Northern Apennines and the Southern Alps, progressively converging one towards the other; b) the inherited structures, mainly derived from the Mesozoic extensional tectonics, are oriented at high angle to the advancing belts. The coexistence of these two factors and their various implications make the Po Valley basin a complex case study that deserves attention. Taking advantage of the recent building of a 3D structural model across the region, we reconstructed the possible geometry and migration pattern of the Tertiary basins that developed at the front of the Northern Apennines and the Southern Alps, as part of the Po Valley tectonic evolution. In addition, a number of sections sliced from the 3D model across selected domains have then been used to restore the present-day structural units to their pre-compressional setting, while highlighting the key stages of their geological history. Results from the model analysis show that the Mesozoic extension-related tectonics and the associated carbonate facies geometry and distribution localized and constrained the Alpine structures inside/around the basin. Their control on the Cenozoic deformation and sedimentation is evident during the Paleogene and the Miocene whereas it becomes more subtle during the Plio-Pleistocene when lithospheric-scale mechanisms need to be invoked. Notwithstanding the model uncertainties and its explicit regional significance, our results may be taken as reference for any foreland-foredeep setting worldwide, especially in complex systems where tectono-sedimentary inhomogeneity is spatially and temporally dominant. Highlights: This paper presents the foreland-foredeep system development of the Po Valley region (northern Italy). The study shows the influence of the Mesozoic tectono-stratigraphy on the basin evolution. The interference between pre-and-post alpine structures is revealed and discussed. Results encourages for application of the methodology to similar settings worldwide.